2018
DOI: 10.1080/20009666.2018.1454789
|View full text |Cite
|
Sign up to set email alerts
|

Pattern, duration of stay, and outcomes of medical admissions: a report from teaching community hospital in Assir region, Saudi Arabia

Abstract: Background: Population-based studies are the gold standard to understand the burden of different diseases, plan health care policy and resource allocation, and provide an accurate estimate of disease several disease indices including mortality. However, population-based studies are difficult to undertake in a resource-limited situation where no robust data bases and disease registries are available. Therefore, hospital-based cohorts may be used to inform about the community health.Objectives: We sought to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…Diabetes was found to increase the risk of hospital admission [8]. A recent study conducted in Saudi Arabia revealed that DM was one of the most common comorbid diseases in hospitalized patients with a percentage of 39.2% [9]. The American Diabetes Association (ADA) recommended starting treatment with insulin when the serum glucose level is persistently high, more than or equals to 180 mg/dL (10.0 mmol/L) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was found to increase the risk of hospital admission [8]. A recent study conducted in Saudi Arabia revealed that DM was one of the most common comorbid diseases in hospitalized patients with a percentage of 39.2% [9]. The American Diabetes Association (ADA) recommended starting treatment with insulin when the serum glucose level is persistently high, more than or equals to 180 mg/dL (10.0 mmol/L) [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, 6.7% were transferred to another health facility, 4.1% left against medical advice, and 5.9% died. 5 Our study shows that 70.3% went home, but 21.7% died. The mortality rate is different and higher in developing countries because of the lack of healthcare availability, as seen in Sudan, Ethiopia, Nigeria, Uganda, and Tanzania, with rates of 4.7%, 12.6%, 16.0%, 17.1%, and 25.6%, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…However, these studies are not available because of a lack of reliable data and expertise, especially in developing countries. 4 , 5 Population‐based studies in our setting will not detail the cause or diagnosis of these diseases. Diseases may determine the pattern of hospital admissions and summarize the health status and disease patterns in the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The different result, probably due to the difference study time is relatively long with this study. Meanwhile more recent study by Al-Ghamdi reported similar finding that cardiovascular diseases were considered the leading cause of hospital admission in a teaching community hospital in Saudi Arabia [14].…”
Section: Figure 2 Ina-cbgs Tariff Per Case-mix Main Groupsmentioning
confidence: 74%